Faktor-Faktor yang Berhubungan dengan Keikutsertaan Kelas Ibu Hamil di Wilayah Kerja Puskesmas Muaro Tembesi - Alexsi Afranika; Rini Mustikasari Kurnia Pratama (Universitas Baiturrahim, 2023)
Pregnant Women Class is a study group for pregnant women with a gestational age between 20 weeks to 32 weeks (before delivery) with a maximum number of 10 participants. The purpose of this study was to determine the factors related to the participation of pregnant women in the working area ofthe Muaro Tembesi Health Center.This research is a type of analytical research with a cross sectional design. The variables studied were age, occupation, availability of information, family support and knowledge, on class participation of pregnant women, population 44 people and the sampling technik uses total sampling so that the research sample 44 people. Sources of data in this study through primary data, data obtained through questionnaires adobted which been tested for validity and reliability, Bivariate and Univariate analysts uses statistic test Chi-Square. The results showed that there was a relationship between age and class participation of pregnant women with (p-value = 0.101>0.05), availability of information (p-value = 0.002>0.05), family support (p-value = 1.00> 0.05), and there is no relationship between work and class participation of pregnant women with (p-value = 0.000>0.05), knowledge (p-value = 0.000>0.05). It is hoped that the results of this research can be an input for health workers, especially midwives to improve the provision of health care, especially in the implementation of guidance, coaching and counseling activities in an effort to increase pregnant women in carrying out class activities for pregnant women.